FFP Portal: A tool for knowledge dissemination of Farmer FIRST Programme - Kumar, Mukesh; Bharadwaj, Anshu; Pal, Soumen; Jain, Rajni; Kumar, Shiv; Gupta, Chetna; Rama, Rama; Chahal, V. P. (Indian Farming, 2019)
The Farmer FIRST (Farm, Innovations, Resources, Science and Technology) Programme (FFP) aims at enriching Farmers–Scientist interface through technology development and application. This programme has been initiated since October, 2016 to provide a platform to farmers and scientists for creating linkages, capacity development, technology adaptation and application, onsite input management, feedback and institution building. Presently 55 FFP are being executed by various ICAR Institutes and Agricultural Universities across the country. Farmer FIRST provides opportunity for the researchers, extension professionals and farmers to work together and find appropriate ways for technology assembly application and feedback to ensure livelihood security.